Social aspects of dental caries in the context of mother-child pairs - MOIMAZ, Suzely Adas Saliba (Faculdade de Odontologia de Bauru da Universidade de São Paulo, 2014)
The relationship between mother and child in the context of oral health has traditionally been exposed by the scientific literature in microbiology, which lacks a broad and necessary discussion of health and illness seen as processes, both biological and social. OBJECTIVE: Investigate the family social determinants associated with the caries history of children and the need for dental treatment (NDT) among their mothers was the objective of this study. MATERIAL AND METHODS: This research employed a cross-sectional study of mother-child pairs living in southern Brazil. Data collection occurred in public institutions of early childhood education. The instruments included a structured questionnaire administered to mothers and clinical oral examinations of the mothers and children. The social variables considered were marital status, maternal education, number of children, income, employment status, and frequency of visits to a dental professional. The measured outcomes were the maternal NDT and child caries history. Data were analyzed by the chi-square test (χ2) and by discriminant analysis. RESULTS: The final sample consisted of 272 mother-child pairs and it was found that the greatest need for treatment was among mothers with low educational level and low family income who rarely or never visited a dentist. Tooth decay was less frequent in only child, and most frequent in children of mothers with low educational attainment, and in children in lower income households who rarely or never visited the dentist. The social determinants of caries in children and of the maternal NDT were similar. It follows that the maternal NDT and caries history among children were strongly associated with maternal education (p<0.0001), household income (p<0.0001), and frequency of visits to a dental professional (0.0018). Caries history among children was also associated with number of children in the household (p<0.0001). CONCLUSIONS: The results suggest that the caries experience in children depended less on the family social variables than on the maternal NDT.